Asociación entre la fórmula digital y las deformidades del antepié en pacientes atendidos en consultorios externos de traumatología y ortopedia - García Chávez, Leonid Joset (2017)
Analyze the digital formula and its association with forefoot deformities and other characteristics such as age and sex in patients seen in outpatient clinics of traumatology and orthopedics. Methods: A prospective cross-sectional study was carried out. The sample was 323 patients served in outpatient traumatology and orthopedics clinics of the Trujillo Regional Hospital during the period February-May 2017, which met the selection criteria. To determine the association, the Chi-square test was used with a statistical significance level of p < 0.05. Results: The Egyptian foot was the most frequent (62.2%). 40.2% showed deformities, being in Quintus Varus (11.8%) followed by Hallux adductus Valgus (10.5%) the most prevalent. Female sex was more predisposed to deformities (p = 0.001); As well as the age, especially of the interval 41-70 years (p < 0.001). The hallux Valgus was associated with the Egyptian foot (p = 0.001) and clawed fingers with the Greek foot (p < 0.001). Forefoot deformities were more frequent in the Egyptian foot (55.4%) and less frequent in the Roman foot (6.2%). Conclusions: A statistically significant association was established between the digital formula and forehead deformities (p <0.001)